Ukrepi notranjeavstrijskih in štajerskih oblasti ob hrvaško-slovenskem kmečkem uporu leta 1573 - Hozjan, Andrej (Kronika (Ljubljana), 2024)
The article presents a few lesser-known and hitherto unknown facts about the time prior to the outbreak of the Croatian-Slovenian peasant revolt of 1573 and its largely overlooked aftermath that marked the final months of that same year. Receiving warnings about a possible outbreak of a plague epidemic in the Styrian city of Graz, Charles II, Archduke of Austria, arrived in Ptuj before the end of 1572. However, once the news reached him about a revolt brewing, he immediately set back to his court, making his journey through Maribor. The article presents the measures that were passed by the sovereign’s office in Celje, the sovereign himself, and the provincial authorities, as well as discusses the correspondence between Celje, Graz, Ljubljana, Zagreb, and indirectly also the imperial court in Vienna. The measures had a significant influence on the course of the revolt and its surprisingly rapid end.
Keywords: 16. st.; 16th cent.; communications; Croatian-Slovenian peasant revolt; hrvaško-slovenski kmečki upor; Inner Austria; kmečki upori; Notranja Avstrija; obveščanje; peasant revolts; postal connections; poštne zveze; Styria; Štajerska